1999
DOI: 10.1590/s0100-879x1999000800009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mercury on the arterial blood pressure of anesthetized rats

Abstract: The available data suggests that hypotension caused by Hg 2+ administration may be produced by a reduction of cardiac contractility or by cholinergic mechanisms. The hemodynamic effects of an intravenous injection of HgCl 2 (5 mg/kg) were studied in anesthetized rats (N = 12) by monitoring left and right ventricular (LV and RV) systolic and diastolic pressures for 120 min. After HgCl 2 administration the LV systolic pressure decreased only after 40 min (99 ± 3.3 to 85 ± 8.8 mmHg at 80 min). However, RV systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…The effect of elemental mercury on cardiovascular function in humans is not well characterized, but there are laboratory animal studies that may shed light on our findings. The general trends observed in our elemental mercury-exposed male population are consistent with animal studies that have reported that high doses of inorganic mercury cause depressed arterial systolic pressure (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999). Differences between elemental mercury and methylmercury effects may be realized at the cellular level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The effect of elemental mercury on cardiovascular function in humans is not well characterized, but there are laboratory animal studies that may shed light on our findings. The general trends observed in our elemental mercury-exposed male population are consistent with animal studies that have reported that high doses of inorganic mercury cause depressed arterial systolic pressure (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999). Differences between elemental mercury and methylmercury effects may be realized at the cellular level.…”
Section: Discussionsupporting
confidence: 90%
“…Though several animal studies have documented that elemental mercury may decrease myocardial mechanical activity, depress heart rate, promote heart arrhythmias, and cause hypotension (Massaroni et al, 1995; Rhee and Choi, 1989; Rossoni et al, 1999), to our knowledge these relationships have not been investigated in an epidemiological study. Accordingly, the goal of this study was to increase understanding of the association between mercury exposure (both methylmercury and elemental mercury) and blood pressure in a cohort of dental professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury per se is reported to induce an endothelial-dependent vasorelaxation and alter structure and function of vascular endothelial cells [7]. Mercury at 5 mg/kg, iv is reported to induce hypotension in rats [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Naganuma et al [124] reported that acute exposure to HgCl 2 (680 ng/kg) increased blood pressure, heart rate, and vascular reactivity to phenylephrine in rats; this increased reactivity seems to depend on an increased generation of free radicals. Perfused hearts from animals exposed acutely to HgCl 2 showed a reduction in left ventricular systolic pressure, heart rate, and atrioventricular conduction delay [125, 126]. …”
Section: Effect Of Mercury On the Cardiovascular Systemmentioning
confidence: 99%